Peremajaan "Brandgang" Sebagai Akses Penunjang Sirkulasi Antar Gang Di Lingkungan Perumahan Babatan Pilang - Heristama Anugerah Putra (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
In the changing times from year to year the development process is always progressing. No exception to the construction of settlements and housing scattered in the city of Surabaya. Arrangement of a housing environment is an important factor in improving the quality of life of residents in society. The residential space pattern in Babatan Pilang still maintains the brandgang system. The function of this brandgang itself is as a fire breaker to slow down or stop fires. Apart from the two main functions, brandgang indirectly also acts as a connection path between alleys or roads. The existing condition of the brandgang in the Babatan Pilang housing complex is not neat and well maintained. In general, the brandgang should not present a tense and frightening atmosphere. The method used is extracting data again looking at the aspects of the problems that exist in relation to the existence of brandgang so far. The function and role of brandgang wherever good and their existence are not necessarily forgotten and are more important, this is because brandgang is one of the main factors of a security system in a settlement or housing. Presenting a neat and orderly brandgang will create a good impression in restoring its main function.